Edgeworthia gardneri (Wall.) Meisn. extract protects against myocardial infarction by inhibiting NF-κB-and MAPK-mediated endothelial inflammation - Wei, Dan; Tang, Le; Su, Lingqing; Zeng, Sufen; Telushi, Ajdora; Lang, Xiaoya; Zhang, Yanli; Qin, Manman; Qiu, Liang; Zhong, Chao; Yu, Jun (Frontiers in Cardiovascular Medicine, 2022)
Experimental and clinical evidence has demonstrated a pivotal role of inflammation in the pathogenesis of ischemic heart disease, and targeting inflammation has been shown to provide clinical benefits for patients with coronary disease. Endothelial cells constitute the majority of non-cardiomyocytes in the heart. Endothelial pro-inflammatory activation is recognized as a critical component in the pathophysiology of cardiovascular disease. The dried flowers of Edgeworthia gardneri (Wall.) Meisn. (EG) have been widely used as Tibetan folk medicine to ameliorate a range of metabolic disorders, such as diabetes mellitus, hyperlipidemia, hypertension, and obesity. However, its role in modulating endothelial inflammation and ischemic heart disease has not been evaluated. Herein, using a preclinical rat model of coronary artery ligation-induced myocardial infarction (MI), we demonstrated that systemic administration of EG extract (EEEG) attenuated ischemic cardiac injury. EEEG reduced myocardial infarct size, improved cardiac function, and ameliorated adverse cardiac remodeling. Moreover, the cardioprotective effects of EEEG were associated with decreased MI-induced myocardial inflammation. Consistent with the anti-inflammatory role of EEEG in vivo, EEEG attenuated TNF-α-stimulated human umbilical vein endothelial cells (HUVECs) activation and monocyte-endothelial cell firm adhesion in vitro. Mechanistically, our data showed that EEEG’s mode of action suppresses the activation of NF-κB, ERK, and p38 MAPK signaling pathways in ECs. Importantly, we demonstrated that EEEG inhibits endothelial inflammation in an NF-κB- and p38 MAPK-dependent manner using pharmacological inhibitors. Collectively, this study identified EG as a potential therapeutic agent in attenuating endothelial inflammation and managing ischemic cardiovascular disease.